The efficacy of different voice treatments for vocal fold polyps: a systematic review and meta-analysis - Latoszek, Ben Barsties von; Watts, Christopher R.; Hetjens, Svetlana; Neumann, Katrin (Journal of Clinical Medicine, 2023)
Background: Vocal fold polyps (VFP) are a common cause of voice disorders and laryngeal discomfort. They are usually treated by behavioral voice therapy (VT) or phonosurgery, or a combination (CT) of both. However, the superiority of either of these treatments has not been clearly established. Methods: Three databases were searched from inception to October 2022 and a manual search was performed. All clinical trials of VFP treatment were included that reported at least auditory-perceptual judgment, aerodynamics, acoustics, and the patient-perceived handicap. Results: We identified 31 eligible studies (VT: n = 47-194; phonosurgery: n = 404-1039; CT: n = 237-350). All treatment approaches were highly effective, with large effect sizes (d > 0.8) and significant improvements in almost all voice parameters (p-values < 0.05). Phonosurgery reduced roughness and NHR, and the emotional and functional subscales of the VHI-30 were the most compared to behavioral voice therapy and combined treatment (p-values < 0.001). Combined treatment improved hoarseness, jitter, shimmer, MPT, and the physical subscale of the VHI-30 more than phonosurgery and behavioral voice therapy (p-values < 0.001). Conclusions: All three treatment approaches were effective in eliminating vocal fold polyps or their negative sequelae, with phonosurgery and combined treatment providing the greatest improvement. These results may inform future treatment decisions for patients with vocal fold polyps.
Gesehen am 04.07.2023